Implementasi Transaksi Tunai dan Non Tunai sebagai Dasar Tata Kelola Pemerintahan yang Baik di BPKAD Kabupaten Bengkalis - Marniati, Putri; Fiddin, Fachroh (Politeknik Negeri Bengkalis, 2023)
This study aims to determine the implementation of cash and non-cash transactions as the basis for good governance at BPKAD Bengkalis Regency. The type of data used in this study is qualitative data. The informants in this study were the Secretary and Treasurer of BPKAD Bengkalis Regency. The data for this research were obtained from the Regional Asset Financial Management Agency (BPKAD) of Bengkalis Regency. Data collection techniques in this study are interviews, observation, and documentation. The research results obtained indicate that the implementation of non-cash transactions in Bengkalis Regency is in accordance with the Bengkalis Regency Regent's Regulations. Even though the cash and non-cash transaction systems are not fully optimal, the governance, OPD, and community have had a very positive impact on the implementation of these non-cash transactions. So that with this application, it can realize good governance, namely, accountability, transparency, effectiveness, and efficiency in regional financial management. Keywords:Â Implementation, Cash Transactions, Non-cashÂ Transactions, GoodÂ Governance.